2022
DOI: 10.3390/ijerph19074139
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Day Training for Managers Reduces Cognitive Stigma Regarding Mental Health Problems: A Randomized Trial

Abstract: Background: Mental illnesses have received increasing attention in the work context in recent years, yet they are still often accompanied by stigma. One starting point for stigma reduction is interventions in the workplace. The present study evaluated a one-day workshop for managers in a large company. Method: Enrolled managers (n = 70) were randomly assigned to the intervention group and the waiting control group. The training included a theoretical section on mental and stress-related diseases as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…A vignette version of the Depression Personal and Perceived Stigma Scale32 showed significant reduction in personal stigma towards people with depression after 6 months and even at 2 years follow-up, but no significant changes were found in the control group. Similarly, the other four studies37 41–43 found significant reduction in stigmatising attitudes in their intervention group post-training, and 1–3 months follow-up, but no significant changes were found in the control groups. The effects of 3–7.5 hours face-to-face trainings were measured by the modified version of the Depression Stigma Personal Subscale,32 the Opening Minds Scale for Workplace Attitude,35 the Opening Minds Stigma Scale for Healthcare Providers44 and the Mental Health Knowledge Scale 43.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…A vignette version of the Depression Personal and Perceived Stigma Scale32 showed significant reduction in personal stigma towards people with depression after 6 months and even at 2 years follow-up, but no significant changes were found in the control group. Similarly, the other four studies37 41–43 found significant reduction in stigmatising attitudes in their intervention group post-training, and 1–3 months follow-up, but no significant changes were found in the control groups. The effects of 3–7.5 hours face-to-face trainings were measured by the modified version of the Depression Stigma Personal Subscale,32 the Opening Minds Scale for Workplace Attitude,35 the Opening Minds Stigma Scale for Healthcare Providers44 and the Mental Health Knowledge Scale 43.…”
Section: Resultsmentioning
confidence: 72%
“…Similarly, the other four studies37 41–43 found significant reduction in stigmatising attitudes in their intervention group post-training, and 1–3 months follow-up, but no significant changes were found in the control groups. The effects of 3–7.5 hours face-to-face trainings were measured by the modified version of the Depression Stigma Personal Subscale,32 the Opening Minds Scale for Workplace Attitude,35 the Opening Minds Stigma Scale for Healthcare Providers44 and the Mental Health Knowledge Scale 43. Fire service line managers (n=106) were randomly assigned to either a 2 days or a 12 hours long training group or a control group (1 hour leaflet session) 39.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, our results suggest that it is crucial that supervisors and coworkers are informed about the challenges linked to motherhood and mental illness to break down the dual stigma working mothers with PPD face. For example, a recent randomized trial by Gast et al (2022) found that managers who were assigned to a 1-day workshop focused on mental illnesses (vs. a control group) reported reduced stigma surrounding mental health. Furthermore, we suspect that greater awareness around mental health can broaden more positive workplaces that are supportive of mental health conditions and employee well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results suggest that it is crucial that supervisors and coworkers are informed about the challenges linked to motherhood and mental illness to break down the dual stigma working mothers with PPD face. For example, a recent randomized trial by Gast et al (2022) found that managers who were assigned This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Practical Implicationsmentioning
confidence: 99%